The Professionalisation of Women's Sport : Issues and Debates. - Bowes, Ali; Culvin, Alex (Emerald Studies in Sport and Gender, 2021)
The Professionalisation of Women's Sportdraws upon the expertise of a range of scholars from the fields of sport sociology, sport history, sport economics to critically discuss the complex and often fragmented histories of women's involvement in professional sport.